Redes aéreas IEEE 802.15.4: tamanho ótimo do pacote e coleta de dados - Wellington Antonio Soares Junior (2014)
The Unmanned Aerial Vehicle (UAV) is becoming popular thanks to technological advances, expanding this technology applications. The rise of IoT drives the development of new low power and low energy consumption radios. One of the main communication protocols for these radios is the IEEE 802.15.4. The union between UAVs and more efficient radio allows the creation of aerial networks, that are wireless sensor networks in which one or more of its nodes is composed of an air vehicle. This new type of mobile sensor network can reduce costs and offer new applications. Thus, it is interesting to develop studies that improve the performance and use of this type of network. By altering the maximum size of the transmitted packet, it is possible to improve the transmission efficiency. Aerial networks can also be used as a new data collection method for wireless sensor networks, in remote or difficult to access zones. The goal of this dissertation is to obtain the optimal packet size that optimize the data packet transmission process. Three analysis methods were employed: use of an analytical model; computer simulation and conducting field experiment. To create the wireless networks sensor nodes, an interface library between the low power radios used in the experiment (XBee 802.15.4) and the used MSP430 microcontroller was developed. It follows that for a better use of the low power radios communication channel, the best packet size is always the one with the greatest possible data body. It was shown that it is possible to implement a wireless sensor networks data collection system with the use of a mobile node. The library which performs the interface between the microcontroller and the radio can be easily expanded and used in other projects containing these two components.